复合材料胶铆混合修理的拉伸性能研究 - 刘礼平; 王宇灿; 原志翔; 徐建新; 鲍蕊; 吴枫 (Jixie qiangdu)
In order to study the influence of different repair methods and different damage sizes on the tensile properties of composite laminates,experimental investigation on static tensile strength was designed and carried out in this paper with five groups of test specimens,including no-damage specimens,adhesive repair specimens and adhesive-rivet hybrid repair specimens with 60 mm and 30 mm circular hole damage for composite aircraft skin.The three-dimensional finite element simulation models of the test specimens were established,to analyze the difference between the five groups of specimens in terms of failure strength,failure mode,stress values and distribution,and critical sites.The results show that the adhesive-rivet hybrid repair method is a better choice which changes the stress distribution of composite repaired parts,reduces the stress concentration effectively in the critical sites,and improves the strength recovery rate of the structure.